Use of species distribution models to study habitat suitability for sustainable management and conservation in the Indian subcontinent: A decade's retrospective - Roy, Sangeeta; Suman, Ashish; Ray, Santanu; Saikia, Surjya Kumar (Frontiers in Sustainable Resource Management, 2022)
Loss of native habitat has been identified as one of the crucial drivers of the growing biodiversity crisis, acting toward the deleterious effects on individual fitness, functional diversity, changes in species richness and community structure. The objective of the study was to review the species distribution modeling works done in the Indian subcontinent throughout the last decade (2012–2021) to highlight the urgent issues of biodiversity conservation and sustainable management. Species distribution model (SDM), ecological niche model (ENM), and habitat suitability model (HSM) are, in general, used to predict the niche of a species. The Scopus search engine result was used for conducting the literature search of peer-reviewed articles. Topics examined included estimation of species' potential distribution area, spread of introduced species, deadly diseases or pests, habitat loss or future range shift of species due to anthropogenic alterations and climate change. The analysis showed that the majority of the works were focused on predicting native species distribution patterns (n = 119, 82%) rather than the invasion of alien species in the native ecosystem (n = 26, 18%) indicating the further scope of research in these areas. The scientific articles highlighted that the modeling results could be utilized efficiently to design conservation areas if not biased toward charismatic species. A coordinating institute at the inter-ministerial level can help to undertake policy-related planning for sustainable management and execution of decisions.